1998
DOI: 10.1021/jp980004e
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Investigations of Zintl Anions Analogous to Ozone

Abstract: Structural features of several species based on Sb3 as a nuclear unit are investigated by ab initio analysis. In particular, the applicability of the Zintl−Klemm−Busmann (ZKB) principle on alkali−antimony clusters of the form A3Sb3 and A4Sb3 + (A = Na, K, Rb) is examined, which have been detected by mass spectrometric measurements. It is shown that basic properties pertaining to geometry, bonding, and stability of these 18 valence electron units display a clear analogy to the respective features of the isoelec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
6
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…The cyclo -Sb 3 in [Sb 3 Au 3 Sb 3 ] 3– also serves as new evidence for the existence of Sb 3 3– fragment upon dissolving K 5 Sb 4 in solvents, which has been put forward for more than 80 years . As predicted by Hagelberg et al, the cyclo -Sb 3 3– is less-preferred compared with the bent ozone style, which was confirmed by Sevov in experiments . Our results indicate that the cyclo -Sb 3 species can be successfully stabilized by the Au 3 ring.…”
supporting
confidence: 82%
See 1 more Smart Citation
“…The cyclo -Sb 3 in [Sb 3 Au 3 Sb 3 ] 3– also serves as new evidence for the existence of Sb 3 3– fragment upon dissolving K 5 Sb 4 in solvents, which has been put forward for more than 80 years . As predicted by Hagelberg et al, the cyclo -Sb 3 3– is less-preferred compared with the bent ozone style, which was confirmed by Sevov in experiments . Our results indicate that the cyclo -Sb 3 species can be successfully stabilized by the Au 3 ring.…”
supporting
confidence: 82%
“…The calculated Wiberg bond order 31 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 The potential energy surface of Sb 3 3− is known to possess two clear minima, representing two Sb 3 3− species with an equilateral triangle structure and a bent one, respectively. 27 Similar to the isoelectronic ozone molecule, the cyclo-Sb 3 3− is less stable than the bent counterpart (∆E = 0.5 eV). Nevertheless, the two cyclo-Sb 3 in [Sb 3 Au 3 Sb 3 ] 3− (Figure 1) are equilateral triangles with D 3h symmetry, hinting that these Sb 3 ligands are not in Sb 3 3− charge state.…”
mentioning
confidence: 99%
“…The distances within the [Pn 3 ] 3- trimers, 2.10 Å for [P 3 ] 3- , 2.374 Å for [As 3 ] 3- , and those of [Bi 3 ] 3- observed in 1 and 2 , are all shorter than the corresponding Pauling's single-bond distances, and manifest their multiple nature. Also, theoretical calculations for [Sb 3 ] 3- have shown that the bent, ozone-like species are more stable than the triangular ones …”
mentioning
confidence: 99%
“…The [Bi 3 ] 3− unit adopts ozone‐like bent configuration, and, therefore, does not appear to be aromatic. Further theoretical calculations for free [Pn 3 ] 3− ions showed that such bent, ozone‐like configuration is lower in energy than the triangular one . It is interesting to note that the reactions of DMF solution of Zintl phase K 3 Pn 7 (Pn=P, As) toward alkynes give rise to 1,2,3‐tripnictolide anions [Pn 3 C 2 H 2 ] − , [Pn 3 C 2 HC 6 H 5 ] − , and [Pn 3 C 2 (C 6 H 5 ) 2 ] − , respectively .…”
Section: π‐Aromatic/antiaromatic Rings In Zintl Clustersmentioning
confidence: 99%
“…Further theoretical calculations for free [Pn 3 ] 3À ions showed that such bent, ozone-like configuration is lower in energy than the triangular one. [27] It is interesting to note that the reactions of DMF solution of Zintl phase K 3 Pn 7 (Pn=P, As) towarda lkynes give rise to 1,2,3-tripnictolide anions[ Pn 3 C 2 H 2 ] À ,[ Pn 3 C 2 HC 6 H 5 ] À ,a nd [Pn 3 C 2 (C 6 H 5 ) 2 ] À ,r espectively. [28] The isolobal relationship between CH group and pentele lement makes these 6 p-electron Pn 3 -containing heterocycles heavier analogues of the ubiquitous aromatic cyclopentadienyl anion [C 5 H 5 ] À .…”
Section: Introductionmentioning
confidence: 99%